The Impact of Forest Encroachment in the Taman Nasional Kerinci Seblat (TNKS) in Kerinci District - Wibi - Wijaya; Trina Febriani; Inoki Ulma Tiara; Yolanda Nur Wijayanti; Muhammad Marzuki Ryanda (Jurnal Mamangan, 2024)
Deforestation within the Taman Nasional Kerinci Seblat (TNKS) in Kerinci Regency is a serious problem that impacts the sustainability of the ecosystem and the social life of the surrounding community. As a conservation area, TNKS plays an important role in preserving biodiversity, regulating water management, and supporting the livelihoods of local communities. However, pressure from agricultural land use, settlement, and economic activities has led to rampant forest encroachment. This research was motivated by increasing forest degradation in the TNKS area, which poses a threat to environmental sustainability and social welfare. The purpose of this study is to analyze the environmental and social impacts of forest encroachment in the foothills of Mount Kerinci, Kerinci Regency. This study uses a qualitative descriptive method with a field study approach through observation, in-depth interviews, and documentation. Data was obtained from the surrounding community, TNKS management officials, and supporting documents, then analyzed qualitatively with an emphasis on the cause-and-effect relationship between encroachment activities and their impacts. The results of the study show that the environmental impacts include loss of forest cover, declining water quality, increased soil erosion, reduced wildlife habitat, and increased risk of ecological disasters such as floods and landslides. Meanwhile, the social impacts that have emerged include increased conflict between the community and TNKS management, shifts in local cultural values, social inequality due to land disputes, and the community's economic dependence on illegal activities in the forest area. Thus, forest encroachment in TNKS not only threatens environmental sustainability but also causes complex social problems for the surrounding community.